The Outcome and cost of Hospital Management of Diabetic’s Foot in Khartoum Main Hospitals In Period from November 2018 to November 2019 - Mourkaz, Abdelaziz Elhadi Yousief; Elmakki, Ahmed Mohamed; Mahdi, Saief aldeen Ibrahim (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Background:  Diabetic foot ulcer is a major complication of diabetes with a high mortality and morbidity and now the most common cause of diabetic related hospitalization and disabling problem leading to amputation of the leg. Objectives: This study aimed to study effective management and outcome of diabetic’s foot in Khartoum main hospitals. Patients and Methods: This was observational, prospective, cross sectional, hospital based study of 133 diabetic patients subjected to hospital management of diabetic foot in five main hospitals at Khartoum State in the period from November 2018 to November 2019. Results: Male to female ratio was 1.9: 1. The mean age of the patients was 53.6±14.0 years, with mean duration of diabetes 11.6±8.3 years.   Surgical management performed for130 patients, 65 (50%) had major amputation, 46(35.4%) debridement and 19(14.6%) minor amputation,    deaths rate were 18(13.5%) in our patients. There was significant association between complications of diabetes ketoacidosis and hypertension related to major amputation and death (P < 0.05). Conclusion: In patient with diabetic foot ulcer in main Khartoum hospitals associated with high rate of major amputation, mortality, long hospital stay and high cost. Diabetic limb ischemia was major risk factor for major limb amputation. There significant association between diabetic ketoacidosis and hypertension related to major amputation and death.